Profil Darah Ayam Petelur yang Diberi Pakan dengan Penambahan Fitobiotik Ekstrak Daun Jati (Tectona grandis Linn. f) - D. N. Edi; M. H. Natsir; I. H. Djunaidi (Jurnal Peternakan, 2020)
This study aimed to evaluate the blood profile of laying hens fed diet supplemented with teak leaves extract phytobiotic. A total of 240 laying hens aged at 30-weeks-old were randomly divided into 24 experimental units (6 dietary treatments with 4 replications). The treatments used were basal diet without any feed additive (control), basal diet + 0.05% antibiotic (AB), and basal diet + teak leaves extract phytobiotic at the level of 0.4%, 0.8%, 1.2%, and 1.6%. Variables observed in this study were erythrocyte, hematocrit, hemoglobin, leukocyte, and thrombocyte. Data were analyzed using analysis of variance, followed by Duncan Multiple Range Test. The results showed that the treatments did not give significant effects (P>0.05) on erythrocyte, hematocrit, hemoglobin, and leukocytes. However, the inclusion of 1.6% teak leaves extract phytobiotic resulted in highly significant increased (P<0.01) on thrombocyte. It could be concluded that the supplementation of teak leaves extract phytobiotic, particularly at the level of 1.6%, could be used to improve blood profile, especially thrombocyte, of laying hens.